Food colloids, biopolymers and materials - Dickinson, Eric; Vliet, Ton van (Royal Society of Chemistry, 2003)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Food scientists aim to control the taste and texture of existing food products and to formulate new structures of high quality using novel combinations of ingredients and processing methods. Food Colloids, Biopolymers and Materials describes the physical chemistry and material science underlying the formulation and behaviour of multi-phase food systems and includes: * descriptions of new experimental techniques * recent food colloids research findings * authoritative overviews of conceptual issues Essential new findings are presented and emphasis is placed on the interfacial and gelation properties of food proteins, and the role of colloidal and biopolymer interactions in determining the properties of emulsions, dispersions, gels and foams. Specific topics include: confocal microscopy; diffusing wave spectroscopy; protein-polysaccharide interactions; biopolymer phase separation; fat crystallization; bubble/droplet coalescence; and bulk and surface rheology. This book is the latest addition to the highly regarded food colloid series published by the Royal Society of Chemistry and is of relevance to those working and researching in food science and surface and colloid science. Visit www.rsc.org/books/8715 for further information.
"The proceedings of the conference Food Colloids, Biopolymers and Materials, held at the Wageningen Centre for Food Sciences, Wageningen, The Netherlands, on 14-17 April, 2002"--Title page verso
Keywords: Colloids -- Congresses.; Food -- Composition -- Congresses.; Biopolymers -- Congresses.; elektronické knihy; electronic books